Bacterial population kinetics in heteroresistant Mycobacterium tuberculosis harbouring rare resistance-conferring mutations in gyrA and rpoB imply an epistatic interaction of mutations in a pre-XDR-TB patient. (17th April 2020) - Yoshida, Shiomi; Iwamoto, Tomotada; Arikawa, Kentaro; Sekizuka, Tsuyoshi; Kuroda, Makoto; Inoue, Yoshikazu; Mitarai, Satoshi; Tsuji, Taisuke; Tsuyuguchi, Kazunari; Suzuki, Katsuhiro
Abstract: Objectives: Bacterial population kinetics of strains harbouring drug resistance-conferring mutations within a patient often show cryptic resistance in clinical practice. We report a case that showed emergence and dominance of Mycobacterium tuberculosis with uncommon rpoB and gyrA mutations, followed by an rpoC compensatory mutation, during treatment. Methods: A pre-XDR-TB patient showed heteroresistance to rifampicin and levofloxacin during treatment as a result of intermittent self-cessation. WGS was applied to investigate intra-host strain composition using five pairs of isolates from sputum samples. Results: The subclone in this study possessed rare mutations conferring resistance to rifampicin ( rpoB V170F) and levofloxacin ( gyrA S91P) and it rapidly outcompeted other subclones during treatment that included levofloxacin but not rifampicin (<7 days). The high-probability compensatory mutation rpoC V483A also emerged and became dominant subsequent to the rpoB V170F mutation. Conclusions: To the best of our knowledge, this is the first case showing the emergence of such a rare variant that dominated the population within a patient during treatment of TB.